"It's the Participation that Motivates Him": Physical Activity Experiences of Youth with Cerebral Palsy and Their Parents. (1st November 2013) - Shimmell, Lorie J.; Gorter, Jan Willem; Jackson, Daphne; Wright, Marilyn; Galuppi, Barb
ABSTRACT Youth with cerebral palsy (CP) face significant barriers to participation in physical activity (PA). There is little information available about the nature of these barriers. Seventeen (17) youth and/or their parents participated in focus groups and individual interviews to identify factors that make it easy or hard to be physically active. Four themes emerged across functional levels: environmental and personal factors, limitations related to impairment in body structure and function, the perception that health benefits alone do not motivate youth to be physically active, and variable preferences for activity delivery. Dialogue with participants revealed that interventions to promote PA in youth should mitigate the interactions between personal and environmental factors that act as barriers to PA, and enhance the interactions that facilitate PA. Partnerships between researchers, policy makers, service providers, and families must be developed to address system barriers and build capacity in youth with CP and their communities.